Pre-Service Mathematics Teachers Learn the Concept of Conic Sections: A Praxeological Analysis of Textbooks - Muhamad Soeleman; Sufyani Prabawanto; Amalia Indrawati G (PRISMA, 2026)
This study investigates how pre-service mathematics teachers (PSMTs) learn conic sections through the task structures in high school mathematics textbooks by applying the Praxeological-Didactical Analysis (PDA) framework. The analysis focuses on identifying the types of tasks (T), techniques (?), technologies (?), and theories (?) in the textbooks used in the Kapita Selekta Matematika Sekolah Lanjutan course. PDA trace the didactical transposition process from scholarly mathematical knowledge to the taught knowledge represented in textbook materials. Using a qualitative document analysis approach, the findings indicate that textbook tasks emphasize procedural and algebraic techniques, with technological and theoretical explanations. The findings reveal that most tasks in the textbooks are dominated by procedural approaches emphasizing algebraic techniques, while the technological and theoretical justifications are often implicit. The study suggests the need for reconstructing praxeology-based task designs that integrate conceptual reasoning and theoretical grounding to strengthen PSMTs’ understanding and didactical competence in teaching conic sections.